HUBUNGAN FAKTOR SOSIODEMOGRAFI DENGAN KUNJUNGAN ANTENATAL CARE - Elika Puspitasari; Mochammad Hakimi; Evi Nurhidayati (Universitas Aisyiyah Yogyakarta, 2017)
Abstact: The purpose of this study was to investigate the association of sociodemographic factors with antenatal care visits. Types of analytic survey research with cross sectional design. Sampling with quota sampling was obtained 100 trimester pregnant women 3. Bivariate analysis using chi-square test. Multivariate analysis with logistic regression test. The results showed that the factors unrelated to ANC were Age (p-value = 0.46), occupation (p-value = 0,55), knowledge (p-value = 0.88), and income -value = 0.22). While the factors of education and distance of pregnancy is related to antenatal care visit (p-value <0,02). Conclusions Age, occupation, knowledge and income are unrelated to antenatal visits whereas education and pregnancy distances are related to antenatal care visits. Keywords: sociodemography, antenatal care visit, pregnancy